SYNTHETIC DYES REACTIVE BLACK 5 AND REACTIVE RED 2 REMOVAL USING BROWN ROT FUNGI ASPERGILLUS NIGER IN SHAKE-FLASK AEROBIC REACTOR - Ayu Prawitasari, Diah
Synthetic dyes are complex organic components that are quite resistant to environmental conditions, making them very damaging to ecological systems. Color removal with biological mechanisms is considered more economical, does not produce toxic by-products, and is more eco-friendly. This study analyzed the removal of synthetic textile colors Reactive Black 5 (RB5) and Reactive Red 2 (RR2) with the biological agent brown weathering fungus Aspergillus niger. This study was conducted aseptically. The incubation process was carried out in a 250 ml Erlenmeyer reactor with total dye solution and 100 ml Potato Dextrose Broth (PDB) medium with optimum conditions of 30oC and initial pH 5,14. The treatment was carried out with preliminary research of dye concentration variations of 200, 100, 50, and 25 ppm. Then, further research by reviewing enzyme activity and fungal growth with variations in shaker rotation of 250, 200, 150, 100, and 50 rpm. The results of preliminary research on color removal for variations in concentration showed that Aspergillus niger was able to remove all concentrations up to ±90%. This preliminary research can determine the maximum concentration capacity for further research, namely the color concentration of 200 ppm. The results of the removal of variations in rotation on both dyes showed that the rotation of 150 rpm (RB5: 93%; RR2: 94%) and 100 rpm (RB5: 95%; RR2: 97%) was most optimal until day 6 compared to the rotation of 250 rpm (RB5: 63%; RR2: 66%), 200 rpm (RB5: 71%; RR2: 70%), and 50 rpm (RB5: 78%; RR2: 89%). Color removal involved the degrading enzymes laccase, LiP and MnP. The highest enzyme activity was obtained in the 100 rpm variation which also correlated with the most optimum color removal. The shaker speed affects the oxygen concentration involved in the system. Sufficient oxygen concentration will increase the removal process by oxidase enzymes that synergize with the contribution of reductase enzymes. The highest enzyme activity at 100 rpm variation was MnP (RB5: 62.2 U/L; RR2: 62.1 U/L), then LiP (RB5: 32.2 U/L; RR2: 32.7 U/L) and laccase (RB5: 16.6 U/L; RR2: 15.7 U/L). The growth of Aspergillus niger fungi correlated with the biomass of pellets produced and influenced the biosorption mechanism. Biosorption mechanism trough fungi biomass pellets can be seen through SEM result. Hyphae filamentous in synthetic dyes treatment have structure changing. Biosorption capacity can be analyze from total removal day-0 until day-2. Biosorption capacity for optimum condition 100 rpm RB5 is 23% and RR2 is 27%. Furthermore, synthetic dyes treatment influences total weight of biomass and specific growth. The specific growth (?) of 250 rpm (RB5: 1.05 day-1 ; RR2: 1.02 day-1 ), 200 rpm (RB5: 0.98 day-1 ; RR2: 1.01 day-1 ), and 50 rpm (RB5: 0.43 day-1 ; RR2: 0.41 day-1 ) tended to be lower than 150 rpm (RB5: 0.88 day-1 ; RR2: 0.882 day-1 ) and 100 rpm (RB5: 0.704 day-1 ; RR2: 0.723 day-1 ). The presence of synthetic dyes can reduce biomass growth because the dyes inhibit growth due to the bonding between cell wall proteins and dyes. FT-IR and GC/MS results showed several groups of intermediate compounds from color biodegradation that can be analyzed for biodegradation pathways. The endproduct from biodegradation gives results of compounds which are less toxic due to aromatic bond cleavage, there are toluene and propanoic acid for posible biodegradation pathway RB5. The reaction kinetics analysis also showed that the color removal by Aspergillus niger that the linear model of zero-order reaction kinetics is a very suitable model for the color removal system by Aspergillus niger in both RB5 and RR2. This kinetic reaction model showed removal dye using biomass fungi is done by co-metabolism reaction.